Enhanced spectrofluorimetric determination of two novel combination therapies for the treatment of benign prostatic hyperplasia containing tamsulosin hydrochloride. (26th March 2018) - El‐Kimary, Eman I.; Khamis, Essam F.; Belal, Saeid F.; Abdel Moneim, Mona M.
Abstract: Two novel combination therapies for the treatment of benign prostatic hyperplasia were analyzed using simple and enhanced spectrofluorimetric methods based on derivative and derivative ratio techniques. The two combinations contained tamsulosin hydrochloride (TAM) as a minor component with tolterodine tartrate (TOL) or solifenacin succinate (SOL). The fluorescence of the three drugs under study was measured in methanolic water solution. For the TAM and SOL mixture, successful resolution between both drugs was achieved by derivative manipulation of both ratio and zero‐order emission spectra with good linearity in the ranges of 0.75–3.50 and 2.5–15.0 μg ml −1 for TAM and SOL, respectively. Extensive emission spectral overlap was observed for the TAM and TOL mixture. Therefore, only derivative application of the ratio emission spectra resolved such overlap and quantitated TAM and TOL simultaneously in the ranges 0.75–3.50 and 2.5–20.0 μg ml –1 for TAM and TOL, respectively. Optimization of various experimental parameters that affected the fluorescence intensity of the three drugs was performed. Successful application of all proposed methods was achieved for analysis of the two drugs in each combination therapy in their laboratory‐prepared mixtures and dosage forms with good accuracy and precision.